2020
DOI: 10.1186/s12866-020-01960-y
|View full text |Cite
|
Sign up to set email alerts
|

The combined utilization of Chlorhexidine and Voriconazole or Natamycin to combat Fusarium infections

Abstract: Background: Fusarium species are the fungal pathogens most commonly responsible for the mycotic keratitis, which are resistant to the majority of currently available antifungal agents. The present study was designed to assess the efficacy of a combination of low doses chlorhexidine with two other commonly used drugs (voriconazole and natamycin) to treat Fusarium infections. Results: We utilized combinations of chlorhexidine and natamycin or voriconazole against 20 clinical Fusarium strains in vitro using a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…As discussed previously ( Jiang et al, 2020 ), survival tests were conducted with sixth instar larvae (300 mg; Sichuan, China) to evaluate the efficacy of MIN as a single-agent and in combination with azole drugs on G. mellonella infected with C. albicans R14, C. parapsilosis N101, C. tropicalis 00279, C. glabrata 05448, and C. auris AR385. Larvae were stored in the dark at room temperature with shavings prior to experimental use, while Candida strains had been grown for 2 days on PDA, after which the colony surface was scraped with a sterile plastic loop, washed two times, and adjusted to 1 × 10 8 cfu/ml using sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed previously ( Jiang et al, 2020 ), survival tests were conducted with sixth instar larvae (300 mg; Sichuan, China) to evaluate the efficacy of MIN as a single-agent and in combination with azole drugs on G. mellonella infected with C. albicans R14, C. parapsilosis N101, C. tropicalis 00279, C. glabrata 05448, and C. auris AR385. Larvae were stored in the dark at room temperature with shavings prior to experimental use, while Candida strains had been grown for 2 days on PDA, after which the colony surface was scraped with a sterile plastic loop, washed two times, and adjusted to 1 × 10 8 cfu/ml using sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical practice, chlorhexidine is probably more often concerned as an adjunctive therapy. One study reported good synergistic antifungal effects of CHX and VCZ, but not of CHX and NAT tested in vitro and in vivo ( G. mellonella model) on the F. solani and oxysporum strains collected from infected corneas, skin, nails, and auditory canals [ 103 ]. A pilot study from Uganda, in which CHX was used as a adjunctive therapy in recalcitrant fungal keratitis not responding to monotherapy with 5% NAT, among others, covered three cases of Fusarium spp.…”
Section: Antisepticsmentioning
confidence: 99%
“…The effect of natamycin on fungal corneal ulcers has been reported by Abhishakth Gerhardt et al, (2019). Jiang et al, (2020) reported synergistic antifungal activity of other antifungal drugs with natamycin against Fusarium sp. Natamycin induced antifungal action against plant pathogenic fungal strain Colletotrichum gloeosporioides has been studied by Liu et al, (2019).…”
Section: Introductionmentioning
confidence: 86%
“…The maximum cumulative release of 90.0 %, 94.1 %, 90.0 %, and 98.2 % was recorded at 144 h in distilled water, PBS, acetone, and ethanol. It can be seen that the initial burst release is an essential criterion of antifungal activity as it helps reach the therapeutic concentration of the drug in a minimal period, followed by constant release to maintain the sustained and controlled release of the drug (Jiang et al, 2020). Antifungal activity of natamycin released in the respective solvents at the respective period was evaluated against the fungal strain by well diffusion assay as described earlier.…”
Section: Release Pro Le Studiesmentioning
confidence: 99%